AN ANALYSIS OF LEXICO – GRAMMATICAL ERRORS IN SPOKEN ENGLISH COMMITTED BY ENGLISH SPEAKING TOURIST GUIDES IN BALI - ., I Gede Bryan Permana Yasa; ., Drs. I Wayan Suarnajaya,MA., Ph.D.; ., Putu Eka Dambayana S., S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Studi ini dimaksudkan untuk (1) mengklasifikasikan kesalahan yang dilakukan oleh pemandu wisata Bahasa Inggris dalam penggunaan Bahasa Inggris lisan di Bali dan (2) Menginvestigasi asal kesalahan yang dilakukan oleh lima pemandu wisata Bahasa Inggris di Bali. Studi ini didesain secara kualitatif. Subyek dari studi ini adalah lima pemandu wisata Bahasa Inggris di Bali. Data dari studi ini adalah kesalahan yang dilakukan oleh lima pemandu wisata Bahasa Inggris di Bali. Data-data dianalisis berdasarkan teori Dulay and Krashen (1982) kesalahan yang dilakukan pemandu wisata diklasifikasikan menjadi empat; peniadaan, pengadaan, kesalahan formasi, dan kesalahan penempatan. Lebih lanjut, asal kesalahan pemandu wisata dikategorikan sebagai interlingual dan intralingual.Kata Kunci : kesalahan, analisa kesalahan, Bahasa Inggris lisan The present study aimed at (1) classifying the errors in spoken English committed by the English speaking tourist guides in Bali and (2) investigating the sources of errors in spoken English committed by the English speaking tourist guides in Bali. This study used qualitative research design. The subjects of the study were the English speaking tourist guides in Bali. The data of the study were the errors made by the guides in spoken descriptive. The data were analyzed based on Dulay and Krashen (1982) the guides’ errors in spoken English were classified into four namely; omission, addition, misformation, and misordering. Further, the sources of the guides’ errors were categorized as interlingual and intralingual sources.keyword : error, error analysis, spoken English